2023
DOI: 10.2106/jbjs.22.00686
|View full text |Cite
|
Sign up to set email alerts
|

Similar Survivorship but Different Revision Reasons for Uncemented Mobile-Bearing and Cemented Fixed-Bearing Medial UKA

Abstract: Background:Long-term survivorship and accurate characterization of revision reasons in unicompartmental knee arthroplasty (UKA) are limited by a lack of long-term data and standardized definitions of revision. The aim of this study was to identify survivorship, risk factors, and reasons for revision in a large cohort of medial UKAs with long-term follow-up (up to 20 years).Methods:Patient, implant, and revision details for 2,015 primary medial UKAs (mean follow-up, 8 years) were recorded following systematic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…Survivorship was 91.7%, and the proportion of patients who were either very satisfied or satisfied with the operatively treated knee was 91% 15 . In a long-term populationbased cohort study of 2,015 patients, cemented fixed-bearing UKAs or mobile-bearing UKAs performed without cement exhibited better implant survivorship compared with cemented mobile-bearing designs at a mean follow-up of 8 years 16 . In a Norwegian Arthroplasty Register report (7,549 Oxford UKAs), investigators found a higher risk of revision for periprosthetic fracture (hazard ratio [HR], 15; p < 0.001) and for infection within 1 year (HR, 3.0; p = 0.001) with use of the uncemented Oxford Partial twin-peg femoral component design compared with the cemented Oxford Partial design.…”
Section: Clinical Results and Outcomesmentioning
confidence: 97%
“…Survivorship was 91.7%, and the proportion of patients who were either very satisfied or satisfied with the operatively treated knee was 91% 15 . In a long-term populationbased cohort study of 2,015 patients, cemented fixed-bearing UKAs or mobile-bearing UKAs performed without cement exhibited better implant survivorship compared with cemented mobile-bearing designs at a mean follow-up of 8 years 16 . In a Norwegian Arthroplasty Register report (7,549 Oxford UKAs), investigators found a higher risk of revision for periprosthetic fracture (hazard ratio [HR], 15; p < 0.001) and for infection within 1 year (HR, 3.0; p = 0.001) with use of the uncemented Oxford Partial twin-peg femoral component design compared with the cemented Oxford Partial design.…”
Section: Clinical Results and Outcomesmentioning
confidence: 97%